From tool to digitized co-conspirator: A reflective analysis of GPT-based engagement with educational equity - Ouedraogo-Thomas, Raketa (American Journal of STEM Education, 2026)
This essay explores artificial intelligence as infrastructure for liberatory leadership through My Partner in Equity, a custom GPT developed in 2023 and refined over 21 months. Drawing on Freire’s critical consciousness, this analysis examines how AI design paradigms can shift from architecture-style (autonomous) to equity-style (human-in-the-loop) approaches. Through documentation across three phases, findings suggest AI’s potential to facilitate transformative dialogue while supporting vocabulary development and critical consciousness. However, tensions arise around emotional authenticity, model transparency, and platform dependence. This work demonstrates “design symbiosis”—mutually beneficial relationships between humans and AI that respect human voice, emotional labor, and ethical boundaries. While acknowledging contradictions of using potentially exploitative AI for liberation goals, this analysis urges educators to view AI as partners in practice.